2016
DOI: 10.15537/smj.2016.2.13013
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Saudi dental students on cultural competency

Abstract: Objectives:To probe dental students’ perceptions on their cultural competency and international student exchange programs as a way of improving cultural competency training.Methods:A cross-sectional survey (n=460) was distributed to predoctoral students at the College of Dentistry, King Saud University, Riyadh, Kingdom of Saudi Arabia in May 2014 at the male and female university campuses. Descriptive statistics were carried out using Statistical Package for Social Sciences (p=0.05).Results:It was found that 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…One study discussed ethical commitment, the limited time spent on ethics education, and the difficulty in assessing ethics in the context of students’ behaviors . Another study further highlighted the pivotal role of instructors and how their actions can influence students’ perceptions of what is ethical in a dental context .…”
Section: Resultsmentioning
confidence: 99%
“…One study discussed ethical commitment, the limited time spent on ethics education, and the difficulty in assessing ethics in the context of students’ behaviors . Another study further highlighted the pivotal role of instructors and how their actions can influence students’ perceptions of what is ethical in a dental context .…”
Section: Resultsmentioning
confidence: 99%
“…In other dental schools around the world, Saudi Arabian dental students reported cultural competence was a highly important topic and acknowledged their school should implement more ways to improve cultural competence 16 . A curriculum review in an Australian university urged for increased transcultural content in the DDS curriculum 13 .…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no magic formula to ensure that the unique cultural needs of every patient are addressed. In line with the literature, the main approaches cited by CS to facilitate the learning of the cognitive basis of cultural competence included a variety of teaching exercises that enable feedback on course content and student response , practical exercises [role playing and simulation] , clinical rotations in culturally diverse communities and self‐evaluation [reflective diaries about personal opinions concerning treating culturally diverse patients and their CC training] , as well as interdisciplinary courses with other health practitioners . It was also suggested that increasing the proportion of students from ethnic minorities within dental schools, and exposure to as wide as possible a variety of cultures may help address challenges associated with cultural diversity and cultural learning .…”
Section: Discussionmentioning
confidence: 99%
“…Methods of tackling the teaching of CC have been researched in the fields of medicine , nursing and dentistry . Despite this, there are reports of a lack of awareness of the importance of cultural competence in dental education .…”
Section: Introductionmentioning
confidence: 99%